Pembelajaran Bahasa Arab Dalam Buku Teori Dasar Nahwu & Sharf Tingkat Pemula Karya Dr. H. Abdul Haris, M.Ag. (Telaah Aspek Materi Ajar & Teknik Penyajian) - Putri Ladya Rausyan Fikri; Fatkhurrohman (DAS Institute, 2024)
Learning Arabic in Indonesia faces several problems, such as lack of student preparation, complexity of the material, and lack of teacher ability in developing teaching materials. One important component is learning material which plays a role in helping teachers explain lessons and students understand the material. Find out what is taught in the book